Sex Discrimination as Perceived by Adult Males and Females, 1985: (New Jersey) - Sigel, Roberta S. ([Verlag nicht ermittelbar], 1989)
This data collection provides information on the ways in which men and women perceive the existence or non-existence of sex discrimination, how they react to it, and how they assign blame for it. The data explored "minority consciousness" among women and investigated how this group-shared consciousness affected women's orientation toward the political system as well as toward each other. Variables designed to measure minority consciousness include respondents' views on the existence of societal, work-related, and domestic sex discrimination, attitudes regarding such discrimination, and the extent to which women identify with other women. Variables regarding personal experiences with sex discrimination and sexual harassment are also included. Other questions explored attitudes toward recent changes in women's status, responsibility for both past and future changes in status, and the effect of such changes on the respondent's own life. Additional information was gathered on the role of the government in bringing about change in the status of women. Demographic variables include sex, age, race, education, religion, marital status, number of and ages of children, occupation, and family and personal income, as well as political party identification and ideology.